Tocilizumab for massive refractory pleural effusion in an adolescent with systemic lupus erythematosus - Arianna De Matteis; Emanuela Sacco; Camilla Celani; Andrea Uva; Virginia Messia; Rebecca Nicolai; Manuela Pardeo; Fabrizio De Benedetti; Claudia Bracaglia (Pediatric Rheumatology Online Journal, 2021)
Abstract Background Pleural effusion in systemic lupus erythematous (SLE) is a common symptom, and recent studies demonstrated that IL-6 has a pivotal role in its pathogenesis. Case presentation We report a case of a 15 years old Caucasian boy with a history of persistent pleural effusion without lung involvement or fever. Microbiological and neoplastic aetiologies were previously excluded. Based on the presence of pleuritis, malar rash, reduction of C3 and C4 levels and positivity of antinuclear antibody (ANA) and anti-double stranded DNA (dsDNA), the diagnosis of juvenile SLE (JSLE) was performed. Treatment with high dose of intravenous glucocorticoids and mycophenolate mofetil was started with partial improvement of pleural effusion. Based on this and on adults SLE cases with serositis previously reported, therapy with intravenous tocilizumab (800 mg every two weeks) was started with prompt recovery of pleural effusion. Conclusion To the best of our knowledge, this is the first case of JSLE pleuritis successfully treated with tocilizumab.